The Way of Life of Tai-Yoh in Khlong Namsai Sub-District Aranyapathet District Sa Kaeo Province - ก้านจักร วชิรวิทย์ (Journal of Humanities and Social Sciences, Rajapruk University, 2015)
This research aims to study 1) To study the history and culture of the Tai-Yoh. 2) To study the changes and the changing way of life of the Times Tai-Yoh. 3) To study inherited way of life of Tai-Yoh Times. The key informants are Tai-Yoh in Khlong Nam Sai Sub-District. Aged 70 years and over 12 people. Data were collected using in-depth interviews. The data obtained from interviews were conducted to analyze the data based on defined objectives. Using theories and related research into ways to analyze the data. And then presents the data obtained by analyzing the content. The results are as fallow: Tai-Yoh is ethnic group Tai-Laos the evacuation from Vientiane to live in Khlong Namsai Sub-District Aranyaprathet District Sa Kaeo Province. People have changed the way of life in case residential pattern, dressing, agriculture and family and ceremony. Processing social change Thailand under development in the government. That rapidly bring to rural area especially industrial infrastructure for growth economy cause adapting the way of life. The succession plans the conservation and promote the traditional the way of life Tai-Yoh from the community and Sub-district Administrative Organization to remain forever.